UPPER RESPIRATORY INFECTIONS IN CHILDREN AND THEIR RESPONSE TOWARDS THE RATIONALE ANTIBIOTIC THERAPY - Imran Ahmed; Muhammad Hanif; Mushtaque Ali Shah; Muhammad Sajid Noor; Tasneem Kauser; Ashique Ali Arain (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Upper respiratory tract is more vulnerable to numerous microbes so Pediatric populations gets easily and frequently infected by these pathogens. Upper respiratory infections Pharyngitis, Tonsillitis and Otitis media are major cause of discomfort in children. Study Aims: This particular research with cross sectional design was aimed for assessing various types of upper respiratory infections   in pediatric patients presented to the outpatient department of Suleman Roshan Medical College, Tando Adam, Sindh, Pakistan. Study Methods: There were 1500 pediatric patients diagnosed as upper RTIs included in the study while all other cases were excluded from this research over a time span of one year using purposive sampling technique. Parents allowed the study with written consent and provided the required data information. The antibiotic response was assessed as resolution of symptoms. Results: The male proportion of patients dominated over female proportion with 824 (54.83%) and 676 (45.07%) respectively.  Under 5years children were 1044(69.4%) and Pharyngitis above 5 years 456(30.6%). Tonsillitis, Pharyngitis and otitis media were the common upper RTIs observed in the studyConclusion: Pharyngitis was most common among upper respiratory infections followed by tonsillitis and otitis media all responded well to Macrolides, Penicillin and Cephalosporin class of antibiotics